2007
DOI: 10.1111/j.1551-2916.2007.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Compounds Prepared in a CaO–Y2O3–SnO2 System

Abstract: Compounds in a CaO–Y2O3–SnO2 system were prepared by a solid‐state reaction at 1673 K. The phase relation in this system was investigated by powder X‐ray diffraction. Besides the previously reported ternary compounds, CaSnO3, Ca2SnO4, Y2Sn2O7, and a quaternary compound Ca0.4Y1.2Sn0.4O3, solid‐solution series of Ca2−xY2xSn1−xO4 with 0≤x≤0.5, and Ca1−yY2ySn1−yO3 with 0≤y≤0.2 and 0.95≤y≤1.0 were found. The cell parameters of these solid‐solution series were refined. The changes of rhombohedral cell parameters in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…According to the phase diagram calculated by Udalov et al for the binary system CaO–Y 2 O 3 only the individual components exist as the phases below 2000 K . These calculations were recently supported by Richter and Gobbels and Kaminaga et al who did not observed binary Ca–Y oxides for the samples calcinated at temperatures of 1500 and 1200 °C, respectively. On the other hand, Maeda et al assumed the formation of CaY 2 O 4 at the temperatures as low as 900 °C.…”
Section: Resultssupporting
confidence: 70%
“…According to the phase diagram calculated by Udalov et al for the binary system CaO–Y 2 O 3 only the individual components exist as the phases below 2000 K . These calculations were recently supported by Richter and Gobbels and Kaminaga et al who did not observed binary Ca–Y oxides for the samples calcinated at temperatures of 1500 and 1200 °C, respectively. On the other hand, Maeda et al assumed the formation of CaY 2 O 4 at the temperatures as low as 900 °C.…”
Section: Resultssupporting
confidence: 70%
“…The same results are described in newer publications investigating the CaO-Y 2 O 3 subsystem at 900°C [7] and 1400°C. [8] The Al 2 O 3 -Y 2 O 3 phase diagram consists of the two components Al 2 O 3 and Y 2 O 3 and three intermediate binary phases, yttrium aluminum monocline (YAM, Y 4 Al 2 O 9 ), yttrium aluminum perovskite (YAP, YAlO 3 ), and yttrium aluminum garnet (YAG, Y 3 Al 5 O 12 ). About the melting behavior and the stability of YAP there is a dispute discussion in former experimental studies.…”
Section: Previous Workmentioning
confidence: 99%
“…In a previous study by the present authors, solid solutions of Ca 2Àx Y 2x Sn 1Àx O 4 (0oxo0.5) were prepared at 1400 1C by solidstate reaction in the system of Ca-Y-Sn-O [12]. The compositions of the single-phase formation and the relationship between the compositions and lattice parameters of Ca 2Àx Y 2x Sn 1Àx O 4 indicated that equi-molar Ca 2+ and Sn 4+ ions were replaced by Y 3+ ions.…”
Section: Introductionmentioning
confidence: 99%